A review of volatile compounds in edible macroalgae. (March 2023) - Li, Shuang; Hu, Meijuan; Tong, Yupei; Xia, Zhangyi; Tong, Yichao; Sun, Yuqing; Cao, Jiaxing; Zhang, Jianheng; Liu, Jinlin; Zhao, Shuang; He, Peimin
Graphical abstract: Highlights: The volatile compounds of different seaweeds were summarized. Introducing the common extraction methods of volatile compounds from seaweeds. Seaweed has broad prospects in the food industry. The flavor of seaweed brings challenges to its application for food industry. Abstract: Seaweeds (green algae, red algae and brown algae) are rich in nutrients, and incorporating algae into the human diet can provide important health benefits. However, consumer acceptance of food is closely related to its flavor, and in this respect, volatile compounds are key factors. This article reviews the extraction methods and composition of volatile compounds from Ulva prolifera, Ulva lactuca, Sargassum spp. and economically valuable cultured seaweeds such as Undaria pinnatifida, Laminaria japonica, Neopyropia haitanensis and Neopyropia yezoensis . Research found that the volatile compounds of the above seaweeds were composed mainly of aldehydes, ketones, alcohols, hydrocarbons, esters, acids, sulfur compounds, furans and small amounts of other compounds. Volatile compounds such as benzaldehyde, 2-octenal, octanal, β-ionone and 8-heptadecene have been identified in several macroalgae. This review argues that more research on the volatile flavor compounds of edible macroalgae is required. Such research could aid new product development or widen applications of these seaweeds in the food or beverage sectors.